Kreativitas Sanggar Sang Citra Budaya Surakarta dalam Pelatihan Tari Masa Pandemi Covid-19 - Hartanto Hartanto (Abdi Seni, 2022)
This report is the result of Community Service with the theme of ‘Creativity of Sang Citra Budaya Art Studio Surakarta in Dance Training during the Covid-19 Pandemic.’ The purpose of the training is to accommodate the talents, abilities and enrichment in the field of dance for the art studio students. The targets of the activity are students and teachers at the art studio. The training activities are carried out using the dialogical method, the lecture method, the demonstration method, and the drill method. The output of this activity is to direct and make students develop creativity in learning dance. The result of the creativity in training activity is the creation of the offering dance “Sesaji Nur Citra Laksita” and Wayang Bocah “Dewa Ruci”.